Is going digital the solution? Evidence from social protection - Krista Alvarenga; Beatriz Burattini; Gabriela Perin (International Policy Centre for Inclusive Growth (IPC-IG), 2022)
This special 50th issue of Policy in Focus provides examples of countries that have digitalised their social protection systems to varying degrees. Its 12 articles provide a glimpse on different building blocks of digital architecture, such as national unique ID systems, tools for registration and payments, the automatisation of eligibility decision-making processes, the existence of digital infrastructure, databases and software, and other aspects.
Keywords: 330; social protection; digitalisation; data security